PENENTUAN KALOR DARI CAMPURAN ARANG TEMPURUNG KELAPA DENGAN CANGKANG KELAPA SAWIT DI TINJAU DARI PERBANDINGAN CAMPURANNYA - Doni Pandra; Sugianto '; Maksi Ginting (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been carried to determine the calory value of the mixture of coconut charcoal and palm oil shells using an experimental method. This experiment used a bomb callorimeter to measure the physical parameters of the sample (callory value, sulfur total, total ash and total moisture of content). Each sample was treated by the same pressure and volume. The samples were taken from two different materials, namely charcoal of coconut shells and oil palm shells. Four different samples were made from combination of grain size ratio of 60 : 40 and 40 : 60. The sample A and C were mixture of coconut shell charcoal and charcoal oil palm shells with 60: 40 ratio, while the sample B and D were mixture of coconut shell Charcoal and charcoal oil palm shells for 40: 60 ratio. Results of the test showed the value of the physical parameters i.e callory value, sulfur total, total ash and total moisture of content respectively for the sample A were 6.379 calories cal/g, 0.18%, 1.43%, and 8.00%, for the sample B were 5.732 calories cal/g, 0.22%, 1.30% and 8,48 %, for the sample C were 5.787 cal/g, 0.20%, 10,91%, and 7.19%, and for the sample D were 5.395 calories cal/g, 0.20%, 11.24%, and 7,07%. The sample A had larger grain density so that the grain samples were more solid. The denser of the material was the higher the value of the heat from the charcoal. From the overall data obtained, it was indicated that the sample A had the highest quality value compared to the other samples.